Propagación in vitro de tres variedades de astromelias (Alstroemeria spp.) con tres dosis de citoquininas en el Laguacoto II, cantón Guaranda provincia Bolívar - Caluña Punina, Dolores Isabel (2022)
The subject of this research was the in vitro propagation of three varieties of Astromelias (Alstroemeria spp.) with three doses of cytokinins in the Laguacoto II biotechnology laboratory. The objectives were: i) To determine the most efficient variety for the in vitro multiplication of the ex-plant. ii) To identify the most adequate dose of cytokinin for a greater development of the ex-plant. iii) To establish the benefit/cost ratio for each of the treatments. The methodology applied was a completely randomized design (CRD) with three replications. Three varieties of Astromelias with three doses of Cytokinins were used. The in vitro propagation of three varieties of astromelias with three doses of cytokinins was evaluated in Laguacoto II, Guaranda canton, Bolivar province. An analysis of variance, Tukey's test at 5% was carried out to compare the averages of factors A, B and AxB. Correlation analysis and simple and multiple regression at 5%. According to the results, there was variability among the treatments. The treatment with the highest number of shoots was Astromelia white + 3mg/lt. Regarding the factors under study, the best factor A was presented in Astromelia white; factor B in explant formation, the best dose 3mg/lt, which is reflected in the results of the number of shoots per explant. The best treatment from the cost-benefit analysis was T5; Astromelia white + 3 mg/lt with RB/C of 2.19; with an RI/C of 1.19 USD. This means that for each dollar invested, there is a profit of $ 1.19.